Potentials of steel slag and copper mine tailings as construction materials: a review - Oluwasola, Ebenezer (2013)
The present rate of utilisation of mine waste in a country like Malaysia is rather below expectation compared with some advanced countries. Many studies concentrate on a better way to increase the usage of industrial byproducts in order to ease disposal problems. Enormous quantities of steel slag and copper mine tailings are deposited in yards, polluting the environment. Researchers need to pay attention to the effective use of industrial byproducts in construction to address economic and environmental concerns. The potential uses of copper mine tailings and steel slag need to be explored and the negative impact of mine tailings should be reduced by exploring potential uses of these waste materials in the construction industry. Although copper tailings have negative effects on the environment owing to their acidic content, they also have some great economic value in terms of valuable metal contents. The engineering properties of steel slag and copper mine tailings were reviewed and their various areas of application are highlighted.